Bulgarian and Romanian naval forces in the face of challenges posed by Russia’s downright aggression against Ukraine in 2022 - Skrzyński, Tomasz (Polityka i Społeczeństwo, 2024)
A comparative analysis of the naval forces of Bulgaria and Romania is warranted by a number of similarities between these countries, e.g. in terms of geopolitics, military aspect, the economy or even religion. Hence the relevance of a comparative analysis of changes in the defence policy and the place of the Naval Force therein. In the 21st century, changes in these navies have been of great importance. They were entailed by efforts to keep up with requirements of contemporary naval warfare. Subsequent challenges were caused by the pandemic and Russia’s aggression against Ukraine. Factors that have a significant effect on the public perception of the Navies in the countries discussed include changes in the recruiting policy as well as economic and social issues besetting Bulgaria and Romania.